PENGARUH PENGGUNAAN LEMBAR KERJA SISWA (LKS) TERHADAP HASIL BELAJAR SELAMA NEW NORMAL PADA MATA PELAJARAN INFORMATIKA - Yelfiyani Yelfiyani; Supriadi Supriadi (JUTECH : Journal Education and Technology, 2021)
This research is motivated by the results of learning Informatics in class X MAN 2 Agam during the current New Normal where learning outcomes are under the Minimum Completeness Criteria (KKM) that have been determined. Problems found, problem-based learning strategies are needed to help teachers in the delivery of learning materials, namely by asking students to solve a problem related to the subject matter so that students can be active in the learning process. The type of research used is Quasi Experiment. The population in this study were students of class X MAN 2 Agam for the 2020/2021 academic year. Sampling is done by purposive sampling technique, namely taking samples with certain considerations. The population of class X is 114 students. Based on the results of the daily test (initial) the average class X IPA was made the Experiment class, while some students from class X IPS/IPK were used as the control class. The data of this study were obtained by a final test in the form of objective questions as many as 25 items that have been tested. Because the value of tcount > ttable, it means that H0 is rejected and H1 is accepted. Based on the above calculations, it can be concluded that tcount > ttable (0.203 > 1.68) where H0 (No Effect of Using Student Worksheets (LKS) on Learning Outcomes During New Normal In Informatics Subjects in MAN 2 Agam) is rejected, then Ha (There is an Influence of Using Student Worksheets (LKS) on Learning Outcomes During New Normal In Informatics Subjects at MAN 2 Agam) is accepted.